The Role of Environment As Third Teacher Towards The Development Of Educational Space For Dyslexic Children (International Journal of Built Environment and Sustainability, 2019)
Educational space that responds towards disable learning student needs is vital for a conducive learning environment. This paper explores on learning spaces for disable children namely the dyslexic in reference to the role of environment as the third teacher towards designing an appropriate educational space to fulfil their needs. Past literature on dyslexia in Malaysia much focuses on the pedagogy and teaching methods rather than discusses the issue of providing better learning space design that caters to the need of dyslexic children towards their psychological well-being. To conduct this study, the qualitative method involving case study as research strategy is used to establish the appropriate learning space design attributes for the dyslexic children. Data sources for this study are obtained from direct observation on three selected case studies of prominent learning disability school found in the global context. There are two key factors that contributed in the learning process and development of learning disability student namely the dyslexic children. These are the non-physical elements comprises of visual cues, auditory, tactile and kinaesthetic approaches as well as physical elements encompasses of density and size including spatial layout arrangement. Findings of the study are in the form of established referential guideline design to inform future designers, builders, education providers and related authority on how to build a conducive learning space environment for the dyslexic children. This is vital in improving the quality of public education infrastructure for dyslexic students in the Malaysian context towards their betterment in the future.
Keywords: learning space design; dyslexia children; environment as third teacher; learning disability